If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 2y = 3y + -20 Reorder the terms: 2y = -20 + 3y Solving 2y = -20 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 2y + -3y = -20 + 3y + -3y Combine like terms: 2y + -3y = -1y -1y = -20 + 3y + -3y Combine like terms: 3y + -3y = 0 -1y = -20 + 0 -1y = -20 Divide each side by '-1'. y = 20 Simplifying y = 20

| 3x+3x=6 | | x^3+15x+5=0 | | x^3+15x+5=11 | | 21-3y=36-6y | | 2y+4(1)=8 | | -2(y-3)=-6y | | 4x-8+6x=13+7x | | 2(f+3)+4f=6+6f | | -35=5-4x | | -2y-6=-6y | | 7(n-6)=-24+n | | 4y=-6 | | -3(1+8v)=-39-6v | | 3(-1)-5y=9 | | -5(1+8b)=-39-6b | | -12-5x=6(8x-2)-4x | | -s^2-13s=0 | | -6(x-3)=-9(-2-3x) | | 3p-2=6p+4 | | 2x+4x=12 | | -12k-11(-k+11)=-(1+9k) | | 3(0)-5y=9 | | t^2+3t=0 | | 3(3)-5y=9 | | 3x+4x=28 | | 9m-7-8=-12(1-m)-2(2m-7) | | 5x+3x=24 | | 2(x+7)=-(x-8) | | a^2-a=0 | | 5(9a+10)=635 | | 5x+4x=9 | | 9+5(1+2n)=6(n-3) | | 3x+2x=15 | | 4(4)=y-7 | | y^2+13y=0 | | -5p-2(2p-5)=9p+10(5-2p) | | 5x+2x=7 | | 11(8+8x)=5(x+1) | | -y^2-6y=0 | | -8(a-7)-4(a-1)=9a-6a | | -b^2+b=0 | | 7+2(5n+2)=-(-11+4n)-4n | | 2x+48=5x+12 | | m^2+2m=0 | | 5x+2x=14 | | 8x-9=5x+3 | | 2x+32=11x-76 | | 6x-2=13x-65 | | b^2+4b=0 | | 7+6x=27+x | | 3(2y+1)=8 | | 65=5k | | 4c+7=35 | | t^2-11t=0 | | -8(x-5)=-7(4+6x) | | 4x+8=89-5x | | 2(a-4)+3a=5a-2 | | 85-6x=8x+15 | | -15a+14=-5(3a+5) | | 8-6x+5=3(4x+5)-8 | | s^2+8s=0 | | -10-5x=14-8x | | 107-5x=2x+23 | | 12k-2(k-11)=-4k+10(k+5) | | 6x+10=-125-9x |